"Is there nothing more practical than a good theory?": Why innovations and advances in health behavior change will arise if interventions are used to test and refine theory - Rothman Alexander J (BMC, 2004)
Abstract Theoretical and practical innovations are needed if we are to advance efforts to persuade and enable people to make healthy changes in their behavior. In this paper, I propose that progress in our understanding of and ability to promote health behavior change depends upon greater interdependence in the research activities undertaken by basic and applied behavioral scientists. In particular, both theorists and interventionists need to treat a theory as a dynamic entity whose form and value rests upon it being rigorously applied, tested and refined in both the laboratory and the field. To this end, greater advantage needs to be taken of the opportunities that interventions afford for theory-testing and, moreover, the data generated by these activities need to stimulate and inform efforts to revise, refine, or reject theoretical principles.